2021
DOI: 10.1002/advs.202103331
|View full text |Cite
|
Sign up to set email alerts
|

A Skin‐Interfaced, Miniaturized Microfluidic Analysis and Delivery System for Colorimetric Measurements of Nutrients in Sweat and Supply of Vitamins Through the Skin

Abstract: Nutrients play critical roles in maintaining core physiological functions and in preventing diseases. Technologies for delivering these nutrients and for monitoring their concentrations can help to ensure proper nutritional balance. Eccrine sweat is a potentially attractive class of biofluid for monitoring purposes due to the ability to capture sweat easily and noninvasively from nearly any region of the body using skin‐integrated microfluidic technologies. Here, a miniaturized system of this type is presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 49 publications
0
60
0
2
Order By: Relevance
“…Sweat is an important body fluid containing a wealth of chemicals reflective of nutritional and metabolic conditions [24][25][26][27] . The progression from blood analyses to wearable sweat analyses could provide great potential for non-invasive, continuous monitoring of physiological biomarkers critical to human health [28][29][30][31][32][33][34][35][36][37][38] . However, currently reported wearable electrochemical sensors focus primarily on a limited number of analytes including electrolytes, glucose and lactate, owing to the lack of a suitable continuous monitoring strategy beyond ion-selective and enzymatic electrodes or direct oxidation of electroactive molecules [25][26][27][34][35][36][37][38][39][40] .…”
mentioning
confidence: 99%
“…Sweat is an important body fluid containing a wealth of chemicals reflective of nutritional and metabolic conditions [24][25][26][27] . The progression from blood analyses to wearable sweat analyses could provide great potential for non-invasive, continuous monitoring of physiological biomarkers critical to human health [28][29][30][31][32][33][34][35][36][37][38] . However, currently reported wearable electrochemical sensors focus primarily on a limited number of analytes including electrolytes, glucose and lactate, owing to the lack of a suitable continuous monitoring strategy beyond ion-selective and enzymatic electrodes or direct oxidation of electroactive molecules [25][26][27][34][35][36][37][38][39][40] .…”
mentioning
confidence: 99%
“…Similarly, no significant change in the current was observed with interfering ion concentrations (100 mM Mg 2+ , 100 mM Ca 2+ , and 160 mM Na + ) cast on the K + selective OECT, as compared to the lowest K + physiological concentration (1 mM) in human sweat (Figure i). However, it is worth mentioning that Mg 2+ and Ca 2+ concentrations in human sweat are significantly lower than 100 mM (Ca 2+ and Mg 2+ ranges in human sweat are 0.2–11 mM and <2.5 mM, respectively). Therefore, both (Na + and K + ) ISM functionalized OECTs are highly selective for specific ion detection without much interference by Mg 2+ , Ca 2+ , K + , and Na + in the physiological condition.…”
Section: Resultsmentioning
confidence: 99%
“…Reeder et al proposed an epidermal patch for colorimetric sensing integrated with microfluidic and water-proof electronic systems that can perform real-time physiological measurements on swimmers and dryland athletes [ 110 ]. In particular, most colorimetry sensing applies epidermal patches as wearable devices, as this device can be used for the single-shot measurement of sweat biomarkers once they change color, as reported by previous studies [ 111 , 112 ].…”
Section: Sweat-sensing Device (Ssd)mentioning
confidence: 99%
“…Colorimetric sensors [ 191 ] and fluorescent sensors [ 231 ] are the forms of optical sensing most found in recent SSDs. Kim et al reported a soft, thin colorimetric patch mounted with a microfluidic device that consists of passive valving [ 112 ]. Flowing sweat in their colorimetry sensing channel changed the color indicators depending on the loss of iron, zinc, calcium, and vitamin C nutrients.…”
Section: Recent Advances Of Ssds: Optimal In Designs Functionalities ...mentioning
confidence: 99%